Water lubrication composite material, preparation method and bearing
By using water-lubricated composite materials made of ultra-high molecular weight polyethylene, composite paraffin microcapsules and carbon fiber, the wear and friction problems of ship stern bearings under low speed and heavy load conditions are solved, and the low coefficient of friction and wear resistance are achieved. , and avoid marine environmental pollution.
Patent Information
- Application Number
- CN202411625183.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
AI Technical Summary
Existing ship stern bearings are prone to intensifying wear and increasing friction coefficient under low speed and heavy load conditions, which affects navigation safety and economy. At the same time, traditional oil lubrication will lead to marine environmental pollution.
Ultra-high molecular weight polyethylene, composite paraffin microcapsules and carbon fiber hot press sintering are used to make water-lubricated composite materials. The outer membrane of microcapsules is prepared by melamine to wrap the paraffin core material to form a stable, dispersed and leak-free micro-lubricated capsule.
It achieves low friction coefficient and wear resistance under high load conditions, avoids the problem of bearing lubrication in some areas caused by uneven lubricant dispersion, and does not pollute the marine environment.
Smart Images

Figure CN119490705A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a water-lubricated composite material and a preparation method thereof, and a bearing. Background Art
[0002] The stern bearing supports the rotation of the stern shaft in the ship and maintains the stable operation of the shaft system. It is one of the important components of the ship's propulsion system. During the operation of the ship, the friction coefficient and wear resistance of the stern bearing are important parameters. Under low-speed and heavy-load conditions such as starting and stopping of ship equipment, the surface of the stern bearing is in a state of boundary lubrication or even dry friction, causing increased wear and increased friction coefficient, which in turn affects the safety and economy of the ship's navigation. At present, the stern bearings of most ships are still mainly made of metal materials, which are oil-lubricated during operation, but will cause pollution to the marine environment. The wood of the iron pear wood is dense, hard, and has good self-lubricating properties and hydrophilicity. Therefore, it is widely used in traditional water-lubricated bearings, but the wood resources of the iron pear wood are scarce and in short supply, while the raw materials of polymer materials are sufficient. Therefore, the development of new polymer materials for water-lubricated bearings has become a hot research field. Summary of the invention
[0003] The purpose of the present invention is to solve the deficiencies of the prior art and provide a water-lubricated composite material and a preparation method and a bearing, which specifically adopts the following technical solutions:
[0004] In one aspect, the present invention provides a method for preparing a water-lubricated composite material, comprising the following steps:
[0005] Ultra-high molecular weight polyethylene, composite paraffin microcapsules and carbon fibers are hot-pressed and sintered to prepare a water-lubricated composite material; the preparation method of the composite paraffin microcapsules comprises the following steps:
[0006] Preparing a mixed solution S1: mixing sodium chloride and nanocellulose crystals in an aqueous solution, adding paraffin and uniformly dispersing the mixture, and adjusting the mixture to be acidic to obtain a mixed solution S1;
[0007] Preparing a mixed solution S2: Under the protection of an inert gas, dissolving melamine in a formaldehyde solution, adjusting the solution to be alkaline, and then reacting the solution at 70° C. to 80° C. to obtain a mixed solution S2;
[0008] Preparation of composite paraffin microcapsules: adding the mixed solution S2 to the mixed solution S1, mixing them evenly, reacting them at 70° C.-80° C., washing the reaction product and drying it to obtain composite paraffin microcapsules.
[0009] The present invention adopts paraffin as core material, introduces sodium chloride and nano cellulose crystals to make paraffin form colloidal particle emulsion in water (paraffin forms a uniformly dispersed state), and then forms a microcapsule outer membrane prepared by melamine to wrap it, so as to prepare the composite paraffin microcapsule of the present invention; the present invention adopts nano cellulose whisker as emulsifier in the preparation process, and the nano cellulose whisker has high aspect ratio and renewability, so that it can not only play an emulsifying role in the microcapsule system used by the present invention, avoiding the introduction of surfactant, but also the microscopic mechanical characteristics brought by the high aspect ratio characteristics can also bring better mechanical properties to the microcapsule system, so that the nano cellulose whisker becomes a part of the microcapsule wall material in the subsequent preparation process, plays a supporting role, and also creates external micro protrusions for the microcapsule, so that after the microcapsule is prepared in the subsequent preparation, the synergistic effect of the composite paraffin microcapsule and the carbon fiber is generated in the ultra-high molecular weight polyethylene matrix.
[0010] In the prior art, liquid lubricants or low-melting-point solid lubricants are often directly added to reduce the friction coefficient. However, in this solution of directly adding lubricants, the compatibility between the lubricant and the base material is often poor. On the one hand, it is very easy to cause phase separation between the lubricant and the base material. The phase separation between the lubricant and the base material will lead to unstable performance of the final product, which will lead to excessive difference in friction coefficients between different positions of the spindle and the bearing in some cases, resulting in local overheating and locking. On the other hand, the lubricant may leak in the base, and the leaked lubricant will reduce the lubrication performance of some areas. In some cases, the leaked lubricant will even change the overall structure of the base material, resulting in tiny cavities in some positions due to the leakage of the lubricant. Such cavities will cause uneven force under high loads, resulting in excessive wear and poor wear rate performance.
[0011] The water-lubricated composite material provided by the present invention uses melamine to prepare the microcapsule outer film to wrap the paraffin core material, so that the paraffin as a lubricant and the ultra-high molecular weight polyethylene as a matrix material can be more closely and evenly combined, so that the paraffin lubricant can be evenly dispersed and fixed in the matrix material through the microcapsules prepared by melamine, and because the microcapsules prepared by melamine wrap the paraffin lubricant, the paraffin lubricant forms stable, dispersed and leak-proof tiny lubricating capsules in the ultra-high molecular weight polyethylene matrix, so that during the movement of the main shaft, when the bearing is worn by the main shaft, the paraffin lubricant can be evenly and stably released in the worn area, so that the main shaft can be evenly lubricated on the entire bearing plane, avoiding the problem of lack of bearing lubrication in some areas due to uneven dispersion of the lubricant in the prior art.
[0012] In some preferred implementations, the mass ratio of sodium chloride to nanocellulose whiskers is 1:1; and / or the mass ratio of paraffin to nanocellulose whiskers is (80-90):1; and / or the pH of the mixed solution S1 is 3-4.
[0013] The nanocellulose whiskers and sodium chloride can, on the one hand, form a uniform emulsion of paraffin, and on the other hand, the nanocellulose whiskers can produce protrusions on the surface of the composite paraffin microcapsules. The formed protrusions have a reinforcing and stabilizing effect, allowing the composite paraffin microcapsules to maintain a relatively stable position during the hot pressing molding production process of water-lubricated materials, thereby making the composite paraffin microcapsules evenly distributed in the water-lubricated composite material.
[0014] In some preferred implementations, the inert gas is nitrogen; and / or the pH of the mixed solution S2 is 8-9.
[0015] In some preferred implementations, the specific conditions for hot pressing sintering are: rising from room temperature to 150°C-200°C within 1 hour to 3 hours, keeping warm for 1 hour to 3 hours, then cooling to 100°C-120°C at a rate of 1°C-5°C / min, keeping warm for 1 hour to 3 hours, and finally cooling to 30°C-50°C.
[0016] In some preferred implementations, the pressure of hot pressing sintering is 10 MPa-20 MPa.
[0017] In one aspect, the present invention also provides a water-lubricated composite material prepared using the above preparation method.
[0018] In some preferred implementations, the water-lubricated composite material comprises, by mass percentage: 60%-80% ultra-high molecular weight polyethylene, 15%-20% carbon fiber, and 5%-25% composite paraffin microcapsules.
[0019] In some preferred implementations, the particle size of the carbon fibers is 10 μm-16 μm.
[0020] The carbon fiber added in the present invention has a similar particle size to the composite paraffin microcapsule, so that the carbon fiber used in the present invention provides lubrication performance for the water-lubricated composite material on the one hand; on the other hand, the carbon fiber also provides strong supporting performance, which can provide a certain stability for the composite paraffin microcapsule. Since the particle size is similar or even slightly larger than the composite paraffin microcapsule, the composite paraffin microcapsule can maintain a stable capsule shape when the water-lubricated material faces a high load, avoiding the premature breakage of the microcapsule. The synergistic effect of the composite paraffin microcapsule and the carbon fiber in the ultra-high molecular weight polyethylene greatly increases the wear resistance under high load conditions.
[0021] In some preferred implementations, the content of the composite paraffin microcapsules is 10%-15% by mass.
[0022] On the other hand, the present invention also provides a bearing made of the water-lubricated composite material.
[0023] The beneficial effects of the present invention are:
[0024] The present invention uses ultra-high molecular weight polyethylene as a matrix material, and through the synergistic effect of adding carbon fiber and composite paraffin microcapsules with a specific structure, the carbon fiber plays a lubricating role in the water-lubricated composite material, and also plays a role in supporting and protecting the composite paraffin microcapsules. The composite paraffin microcapsules, due to their specific structure and particle size, enable their micro-protrusion structure to play a fixing role in the water-lubricated composite material and slowly release the lubricant after being worn. In addition, the particle size is just suitable for matching with the carbon fiber, so that the composite paraffin microcapsules can bring excellent performance to the water-lubricated composite material under the support of the carbon fiber, so that the water-lubricated composite material provided by the present invention has a low friction coefficient and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Shown is an electron microscope photograph of the composite paraffin microcapsule prepared in Example 2;
[0026] Figure 2 Shown is the particle size distribution diagram of the composite paraffin microcapsules prepared in Example 2;
[0027] Figure 3 Shown is the microcapsule profile of the composite paraffin microcapsules prepared in Example 2 after the friction coefficient test. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0029] Example 1
[0030] A water-lubricated composite material, the preparation method of which comprises the following steps:
[0031] The ultra-high molecular weight polyethylene, carbon fiber and composite paraffin microcapsules are mixed evenly, wherein, by mass percentage, the ultra-high molecular weight polyethylene content is 80%, the carbon fiber content is 15%, and the composite paraffin microcapsules are 5%; then the mixed powder is transferred to a cylindrical mold with a diameter of 30mm for hot pressing and sintering, the pressure is 20MPa, starting from room temperature, rising to 200℃ at a uniform speed in 3 hours, keeping warm for 2 hours, then cooling at a rate of 5℃ / min, and keeping warm at 120℃ for 3 hours. After cooling to 30℃, demoulding, polishing, and obtaining an ultra-high molecular weight polyethylene composite material; then using a CNC machine tool to process it into a bearing with an outer diameter of 25mm and an inner diameter of 21mm (for the preparation of bearings).
[0032] The preparation method of the composite paraffin microcapsules comprises the following steps:
[0033] Prepare mixed solution S1: Take 0.42g of sodium chloride and 0.42g of nanocellulose whiskers, dissolve them in 84mL of deionized water, and stir until they are completely dissolved to form an aqueous solution; then add 36g of paraffin and heat until the paraffin is completely melted to form a mixed solution, and use an ultrasonic oscillator to sonicate the obtained mixed solution for 15 minutes to form a uniform solution, and then use HCl solution (2mol / L) to adjust the pH value of the solution to pH = 3.5.
[0034] Prepare mixed solution S2: Take 2.7g of melamine, put it into a 100mL three-necked bottle, install a reflux condenser, and add 0.5g / mL formaldehyde solution while stirring until the solid in the bottle is completely dissolved, then add 1.0mol / L sodium hydroxide aqueous solution to the bottle until the pH = 8, then heat to 80°C and react for 5 hours.
[0035] Preparation of composite paraffin microcapsules: The obtained mixed solution S2 was added to the prepared mixed solution S1, and the mixed liquid was reacted at 80° C. for 3 hours. After the reaction was completed, it was filtered, washed with deionized water several times, and dried in a vacuum drying oven to obtain composite paraffin microcapsules.
[0036] Example 2
[0037] A water-lubricated composite material, the preparation method of which comprises the following steps:
[0038] Ultra-high molecular weight polyethylene, carbon fiber and composite paraffin microcapsules (prepared in the same manner as in Example 1) were mixed uniformly, wherein, by mass percentage, the ultra-high molecular weight polyethylene content was 70%, the carbon fiber content was 15%, and the composite paraffin microcapsules were 15%; then the uniformly mixed powder was transferred to a cylindrical mold with a diameter of 30 mm for hot pressing and sintering, with a pressure of 20 MPa, starting from room temperature, rising uniformly to 200°C in 3 hours, and heat preservation for 2 hours, and then cooling at a rate of 5°C / min, and heat preservation at 120°C for 3 hours. After cooling to 30°C, demoulding was performed, and an ultra-high molecular weight polyethylene composite material was obtained after polishing; then a CNC machine tool was used to process the bearing bush with an outer diameter of 25 mm and an inner diameter of 21 mm.
[0039] Figure 1 The electron microscope photo of the composite paraffin microcapsule prepared in Example 2 is shown. In the photo, it can be clearly observed that there are micro-protrusion structures on the surface of the composite paraffin microcapsule provided.
[0040] Figure 2 The particle size distribution of the composite paraffin microcapsules prepared in Example 2 is shown in FIG. Figure 2 From the particle size distribution diagram, it can be seen that the prepared composite paraffin microcapsule particles are mainly concentrated around 10μm-15μm, and the median particle size is 15μm.
[0041] Combination Figure 1 and Figure 2 It is precisely because the water-lubricated composite material provided by the present invention contains composite paraffin microcapsules with micro-protrusions, and the size of such microcapsules is used together with carbon fibers of similar size, that the carbon fibers not only provide a lubricating effect, but also, due to the similar particle size, bring a supporting synergistic effect to the composite paraffin microcapsules.
[0042] Example 3
[0043] A water-lubricated composite material, the preparation method of which comprises the following steps:
[0044] Ultra-high molecular weight polyethylene, carbon fiber and composite paraffin microcapsules (prepared in the same manner as in Example 1) were mixed uniformly, wherein, by mass percentage, the ultra-high molecular weight polyethylene content was 60%, the carbon fiber content was 15%, and the composite paraffin microcapsules were 25%; then the uniformly mixed powder was transferred to a cylindrical mold with a diameter of 30 mm for hot pressing and sintering, with a pressure of 20 MPa, starting from room temperature, rising uniformly to 200°C in 3 hours, and heat preservation for 2 hours, and then cooling at a rate of 5°C / min, and heat preservation at 120°C for 3 hours. After cooling to 30°C, demoulding was performed, and an ultra-high molecular weight polyethylene composite material was obtained after polishing; then a CNC machine tool was used to process the bearing bush with an outer diameter of 25 mm and an inner diameter of 21 mm.
[0045] Comparative Example 1
[0046] A water lubricating material, the preparation method of which comprises the following steps:
[0047] The ultra-high molecular weight polyethylene powder was transferred to a cylindrical mold with a diameter of 30mm for hot pressing and sintering at a pressure of 20MPa. The temperature was raised to 200℃ at a constant speed over 3 hours from room temperature, and kept at that temperature for 2 hours. Then the temperature was lowered at a rate of 5℃ / min and kept at 120℃ for 3 hours. After cooling to 30℃, the mold was removed and polished to obtain an ultra-high molecular weight polyethylene composite material; it was then processed into a bearing with an outer diameter of 25mm and an inner diameter of 21mm using a CNC machine tool.
[0048] Comparative Example 2
[0049] A water-lubricated composite material, the preparation method of which comprises the following steps:
[0050] The ultra-high molecular weight polyethylene and carbon fiber are mixed evenly, wherein the ultra-high molecular weight polyethylene content is 85% and the carbon fiber content is 15% by mass percentage; then the mixed powder is transferred to a cylindrical mold with a diameter of 30mm for hot pressing and sintering, with a pressure of 20MPa, starting from room temperature, rising to 200℃ at a constant speed in 3 hours, keeping the temperature for 2 hours, then cooling at a rate of 5℃ / min, and keeping the temperature at 120℃ for 3 hours. After cooling to 30℃, demoulding and polishing are performed to obtain an ultra-high molecular weight polyethylene composite material; then a CNC machine tool is used to process it into a bearing with an outer diameter of 25mm and an inner diameter of 21mm.
[0051] Comparative Example 3
[0052] A water-lubricated composite material, the preparation method of which comprises the following steps:
[0053] The ultra-high molecular weight polyethylene and glass fiber are mixed evenly, wherein the ultra-high molecular weight polyethylene content is 85% and the glass fiber content is 15% by mass percentage; then the mixed powder is transferred to a cylindrical mold with a diameter of 30mm for hot pressing and sintering, with a pressure of 20MPa, starting from room temperature, rising to 200℃ at a constant speed in 3 hours, keeping the temperature for 2 hours, then cooling at a rate of 5℃ / min, and keeping the temperature at 120℃ for 3 hours. After cooling to 30℃, demoulding and polishing are performed to obtain an ultra-high molecular weight polyethylene composite material; then a CNC machine tool is used to process it into a bearing with an outer diameter of 25mm and an inner diameter of 21mm.
[0054] Comparative Example 4
[0055] A water-lubricated composite material, the preparation method of which comprises the following steps:
[0056] The ultra-high molecular weight polyethylene and aramid fiber are mixed evenly, wherein the ultra-high molecular weight polyethylene content is 85% and the aramid fiber content is 15% by mass percentage; then the mixed powder is transferred to a cylindrical mold with a diameter of 30mm for hot pressing and sintering, with a pressure of 20MPa, starting from room temperature, rising to 200℃ at a constant speed in 3 hours, keeping warm for 2 hours, then cooling at a rate of 5℃ / min, and keeping warm at 120℃ for 3 hours. After cooling to 30℃, demoulding and polishing are performed to obtain an ultra-high molecular weight polyethylene composite material; then a CNC machine tool is used to process it into a bearing with an outer diameter of 25mm and an inner diameter of 21mm.
[0057] Performance testing and result analysis
[0058] Friction coefficient test: The test was conducted using a ring block tester, with the friction pair being a 40mm diameter tin bronze shaft, a rotation speed of 50rpm, a load of 150N, a load of 0.5MPa, and a linear speed of 0.1m / s. A 3% NaCl solution was selected as the test environment. The experimental results are shown in Table 1.
[0059] Wear rate measurement: The wear rate of each embodiment and comparative example after the friction coefficient test was measured using a white light diffractometer. The measurement results are shown in Table 1.
[0060] Table 1
[0061] Friction coefficient Wear rate Example 1 0.043 <![CDATA[3.01×10 -6 mm 3 / (N.M)]]> Example 2 0.027 <![CDATA[1.11×10 -6 mm 3 / (N.M)]]> Example 3 0.030 <![CDATA[1.81×10 -6 mm 3 / (N.M)]]> Comparative Example 1 0.115 <![CDATA[1.14×10 -5 mm 3 / (N.M)]]> Comparative Example 2 0.063 <![CDATA[5.62×10 -6 mm 3 / (N.M)]]> Comparative Example 3 0.070 <![CDATA[6.06×10 -6 mm 3 / (N.M)]]> Comparative Example 4 0.075 <![CDATA[6.65×10 -6 mm 3 / (N.M)]]>
[0062] As can be seen from Table 1, the overall performance of Examples 1-3 is significantly better than that of Comparative Examples 1-4. Compared with Comparative Example 1 made of pure ultra-high molecular weight polyethylene without adding any other components, the performance of Examples 1-3 is significantly ahead, indicating that the technical solution provided by the present invention greatly improves the performance of materials made of pure ultra-high molecular weight polyethylene in the prior art; the performance gap between Examples 1-3 and Comparative Example 2 is the smallest. According to analysis, Comparative Example 2 uses the same carbon fiber additive as Examples 1-3, but due to the lack of composite paraffin microcapsules, there is still a performance gap; the synergistic effect of carbon fiber and composite paraffin microcapsules in Examples 1-3 makes the friction coefficient of Examples 1-3 more superior than that of Comparative Examples 3 and Comparative Example 4 using other fibers. The addition of composite paraffin microcapsules can significantly reduce the friction coefficient because the composite paraffin microcapsules on the surface of the sample are worn out during the friction process, and the released paraffin is dispersed from the surface with the relative movement of the friction pair, acting as a lubricant.
[0063] In Examples 1-3, when only 5% of composite paraffin microcapsules were added to Example 1, the friction coefficient was reduced to 0.043. Compared with the addition of carbon fiber, the comparative example 2 without adding composite paraffin microcapsules has a significant performance improvement; the water-lubricated composite material (Example 2) doped with 15% composite paraffin microcapsules, 15% carbon fiber and 70% ultra-high molecular weight polyethylene has a better friction coefficient of 0.027; the water-lubricated composite material (Example 3) made of 25% composite paraffin microcapsules, 15% carbon fiber and 60% ultra-high molecular weight polyethylene has a slightly improved friction coefficient compared with Example 2. According to analysis, Example 3 adds 25% of composite paraffin microcapsules, resulting in uneven distribution of composite paraffin microcapsules in some positions in the water-lubricated composite material, so slight aggregation occurs, affecting its rupture and release during the friction process, thereby affecting the formation of the lubricating film, thereby causing the friction coefficient of Example 3 to increase, proving that in the present invention, excessive addition will lead to performance degradation. Therefore, in the technical solution of the present invention, the addition amount of composite paraffin microcapsules should not exceed 25%.
[0064] The wear rates of Examples 1-3 and Comparative Examples 1-4 after the friction coefficient test were measured by white light diffractometer, and the specific data are shown in Table 1. The wear rate of Examples 1-3 is significantly lower than that of Comparative Examples 1-4, indicating that the carbon fibers and composite paraffin microcapsules in the water-lubricated composite material prepared by the technical solution provided by the present invention significantly improve the wear resistance. Compared with Comparative Example 1, the wear rate of Examples 1-3 is even one order of magnitude higher, indicating that the addition of carbon fibers and composite paraffin microcapsules in Examples 1-3 has a huge impact on the performance of the ultra-high molecular weight polyethylene matrix material; compared with Comparative Example 2, although carbon fibers are also added in Examples 1-3, the synergistic effect of the composite paraffin microcapsules and carbon fibers in Examples 1-3 makes the performance of Examples 1-3 still significantly improved relative to Comparative Example 2, even in Example 1, which only adds 5% of the composite paraffin microcapsules, the wear rate is only 3.01×10 -6 mm 3 / (NM), while the wear rate of comparative example 2 is 5.62×10 -6 mm 3 / (NM), which shows that the composite paraffin microcapsules significantly improve the wear resistance of the overall material; compared with comparative example 2, the wear rate data of comparative examples 3 and 4 are more different from those of examples 1-3, indicating that the carbon fibers used in examples 1-3 bring the performance of other fibers. Therefore, in terms of wear resistance, the reason why examples 1-3 are better than comparative examples 1-4 is that during the friction process of the water-lubricated composite material provided by the present invention, the paraffin released by the composite paraffin microcapsules can fill the wear furrows generated by abrasive wear, effectively reducing the aggravation of wear, so that the wear rate is significantly reduced.
[0065] In Example 1, due to the low content of composite paraffin microcapsules added, the lubricating effect of the composite paraffin microcapsules in Example 1 is relatively limited, so in Examples 1-3, the wear rate of Example 1 is relatively large; in Example 3, due to the addition of too many composite paraffin microcapsules, the composite paraffin microcapsules in Example 3 are slightly aggregated, making the material of Example 3 uneven during the wear process, resulting in an increase in the wear rate; the wear rate of Example 2 is the lowest among Examples 1-3, because Example 2 selects an appropriate proportion of the ratio, so that under the experimental environment of the friction coefficient test of the present invention, the synergistic effect of the composite paraffin microcapsules and the carbon fibers makes the water-lubricated composite material have both the two advantages of low friction coefficient and low wear rate, and therefore has better performance effects.
[0066] Figure 3 The wear scar area produced by the water-lubricated composite material prepared in Example 2 after the friction coefficient test is Figure 3 The profile of lubricant release from the composite paraffin microcapsules can be clearly seen.
[0067] Although the description of the present invention has been quite detailed and specifically describes several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, but should be regarded as providing a broad possible interpretation of these claims in view of the prior art by reference to the appended claims, thereby effectively covering the intended scope of the present invention. In addition, the above description of the present invention is based on the embodiments foreseeable by the inventor, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that have not yet been foreseen may still represent equivalent changes to the present invention.
Claims
1. A method for preparing a water-lubricated composite material, characterized in that: The following steps are involved: The water-lubricated composite material is prepared by hot-pressing and sintering ultra-high molecular weight polyethylene, composite paraffin microcapsules and carbon fibers; The preparation method of the composite paraffin microcapsule comprises the following steps: Preparing a mixed solution S1: mixing sodium chloride and nanocellulose crystals in an aqueous solution, adding paraffin and making them evenly dispersed, and adjusting to acidity to obtain the mixed solution S1; Preparing a mixed solution S2: Under the protection of an inert gas, dissolving melamine in a formaldehyde solution, adjusting the solution to be alkaline, and then reacting the solution at 70° C. to 80° C. to obtain the mixed solution S2; Preparation of the composite paraffin microcapsules: adding the mixed solution S2 to the mixed solution S1, mixing them evenly, reacting them at 70° C.-80° C., washing the reaction product and drying it to obtain the composite paraffin microcapsules.
2. The method for preparing a water-lubricated composite material according to claim 1, characterized in that: The mass ratio of the sodium chloride to the nanocellulose whiskers is 1:1; and / or the mass ratio of the paraffin wax to the nanocellulose whiskers is (80-90):1; and / or the pH of the mixed solution S1 is 3-4.
3. The method for preparing a water-lubricated composite material according to claim 1, characterized in that: The inert gas is nitrogen; and / or the pH of the mixed solution S2 is 8-9.
4. The method for preparing a water-lubricated composite material according to claim 1, characterized in that: The specific conditions of the hot pressing sintering are: raising the temperature from room temperature to 150°C-200°C within 1 hour-3 hours, keeping the temperature for 1 hour-3 hours, then cooling to 100°C-120°C at a rate of 1°C-5°C / min, keeping the temperature for 1 hour-3 hours, and finally cooling to 30°C-50°C.
5. The method for preparing a water-lubricated composite material according to claim 1, characterized in that: The hot pressing sintering pressure is 10MPa-20MPa.
6. A water-lubricated composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.
7. The water-lubricated composite material according to claim 6, characterized in that: In terms of mass percentage, the ultra-high molecular weight polyethylene accounts for 60%-80%, the carbon fiber accounts for 15%-20%, and the composite paraffin microcapsule accounts for 5%-25%.
8. The water-lubricated composite material according to claim 7, characterized in that: The particle size of the carbon fiber is 10 μm-16 μm.
9. The water-lubricated composite material according to claim 7, characterized in that: Calculated by mass percentage, the content of the composite paraffin microcapsules is 10%-15%.
10. A bearing, characterized in that: The water-lubricated composite material comprises the water-lubricated composite material according to any one of claims 6 to 9.
Citation Information
Cited By
Self-lubricating composite material, preparation method thereof and water-lubricated bearing
CN120758018A
Self-lubricating composite material, method for manufacturing same and water-lubricated bearing
CN120758018B
Self-lubricating coating suitable for atmosphere and seawater environment and preparation method thereof
CN121203509A